Allochronic reproductive cycles among colonies of the Caribbean octocoral Antillogorgia americana - Lasker, Howard R.; Calderón, Julio (Invertebrate biology, 2024)
The reproductive biology of the branching octocoral Antillogorgia americana was studied at a site on the Caribbean coast of Panama in 1990–1991 by examining the reproductive status of 11 colonies across 14 months. Colonies were gonochoric. The presence of large and mature eggs or spermaries was allochronic across colonies and months, with peak gonad volumes occurring in months ranging from October through May. Reproductive effort varied between branches on a colony, with variation between branches and branchlets accounting for 25% of the random variation between polyps. Branchlets at the tip of the colony had fewer mature eggs than those lower on the branch, and polyps at the tips of the branchlets had fewer still. Although the simultaneous release of eggs and sperm is critical to reproductive success, the lack of synchrony among colonies on the scale of months may reflect less need for all colonies to spawn in a single event among abundant species that release large numbers of gametes. Such a strategy also spreads the risk of reproductive failure due to environmental conditions during any single month. The presence of multiple spawning episodes can also drive the reproductive isolation of populations and may reflect the presence of cryptic species within the taxon. Studies of reproductive timing can be an important adjunct in identifying variation in life history strategies as well as assessing the validity of species boundaries.